MALROTATION OF GUT WITH HORSE SHOE KIDNEY - Nayab Alia; Irshad Ahmed (Journal of University Medical & Dental College)
ABSTRACT We report case of ma I rotation of gut with horse shoes kidney. Plain abdominal x-ray reveals no pneumo-peritoneum, abnormal calcification, and abnormal gut loop seen. Whereas on barium study, small gut situated in right side of abdomen with ileo-cecal junction located in Left iliac fossa. Complementary gray scale ultrasound done, no gut mass/dilatation, vicero-megaly appreciated however shows horse shoe kidney. CT shows also horse shoe kidney. Abreviations: CT-computed topography